Analisis Kepuasan Pengguna Website Repository Universitas Amikom Purwokerto menggunakan Metode System Usability Scale (SUS) - Nur Adiya, Az Zahra Dwi; Anindya Fidela; Dea Lili Anggraeni; Ito Setiawan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
This study aims to analyze user satisfaction with the Universitas Amikom Purwokerto repository website using the System Usability Scale (SUS) method. In the digital era, online repositories play a crucial role as a platform for storing, managing, and distributing academic work, supporting academic activities and knowledge exchange. However, observations indicate that the repository website faces challenges in accessibility, including unintuitive navigation, difficult-to-understand menus, and limited language options, as it is only available in English. Through a SUS survey involving 100 respondents, an average SUS score of 46 was obtained, falling into the